2020
DOI: 10.3390/healthcare9010030
|View full text |Cite
|
Sign up to set email alerts
|

The Artificial Intelligence in Digital Pathology and Digital Radiology: Where Are We?

Abstract: Thanks to the incredible changes promoted by Information and Communication Technology (ICT) conveyed today by electronic-health (eHealth) and mobile-health (mHealth), many new applications of both organ and cellular diagnostics are now possible [...]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 9 publications
0
13
0
1
Order By: Relevance
“…We are undoubtedly about to face another important change in the world of digital radiology [ 14 ]: the introduction of AI in clinical practice. During the pandemic, the importance and potential of AI clearly emerged in two sectors of digital radiology: chest CT and chest radiography [ 15 , 16 , 17 , 18 , 43 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We are undoubtedly about to face another important change in the world of digital radiology [ 14 ]: the introduction of AI in clinical practice. During the pandemic, the importance and potential of AI clearly emerged in two sectors of digital radiology: chest CT and chest radiography [ 15 , 16 , 17 , 18 , 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Those imaging sectors using DICOM are united under the hat of digital radiology [ 10 , 11 , 12 , 13 ]. Now, we are facing the possible impact of research on the health domain [ 14 ]. An important engine in this context is represented by the research efforts during the COVID-19 pandemic.…”
Section: Introductionmentioning
confidence: 99%
“… 14 , 15 Use of technology especially smartphones and social media for the intention of education is the new trend and is supported by research also where students can improve their learning process and it also complemented the conventional methods. 16 , 17 …”
Section: Discussionmentioning
confidence: 99%
“…14,15 Use of technology especially smartphones and social media for the intention of education is the new trend and is supported by research also where students can improve their learning process and it also complemented the conventional methods. 16,17 Efficient use of e-learning apps like MS Office, zoom, teams, canvas, google Classroom, LMS, and access to online study material/power point presentations showed an overall better response in all students but was more in 3rd-semester students as compare to 1st-semester students. These findings are consistent with studies done in private institutes where due to the availability of resources these institutes were able to develop online teaching material on time as they had both monetary and human resources to embark on this difficult venture.…”
Section: A H E a D O F P R I N Tmentioning
confidence: 99%
“…The radiology and pathology workflow can certainly benefit from a routine use of Artificial Intelligence. The advantages that could derive from this seem important [ 1 ]. They range from lightening the workload to quality control of the instrumentation.…”
Section: Introductionmentioning
confidence: 99%